MULTIPLEX PCR ASSAY FOR TOXINOTYPING CLOSTRIDIUM PERFRINGENS ISOLATES OBTAINED FROM HERBS - Wangroongsarb, Piyada; Jittaprasatsin, Chutima; Kamthalang, Thanitchai; Cheunban, Nattapong; Sangkitporn, Somchai; Sriyapai, Thayat (Srinakharinwirot University Journal of Sciences and Technology, 2021)
Two hundred and forty samples of herbs were collected by the Department of Medical Sciences from 2012-2019 to detect Clostridium perfringens by conventional culture method and molecular typing by multiplex PCR. Four major toxin genes (cpa, cpb, etx and iA) and an enterotoxin gene (cpe) from C. perfringens isolates were detected. In this study, C. perfringens isolates were detected in 112 (46.67 %) herb samples by culture method, all of which were genotyped as C. perfringens type A. However, 6 of all type A isolates were positive for the enterotoxin-encoding gene (cpe gene). Enterotoxin-producing C. perfringens were found in 4 types of herbs including wasting disease drug (2 samples), veld grape (1 sample), sweet leaf (2 samples) and turmeric (1 sample). The monitoring of C. perfringens strains by molecular techniques for typing and identifying toxin-producing isolates is useful for the epidemiology data and control the quality of herbal products to meet the standards legal requirements.